2017
DOI: 10.1093/femsle/fnx202
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a mutarotase gene involved in D-galactose utilization in Aspergillus nidulans

Abstract: Aldose 1-epimerases or mutarotases (EC 5.1.3.3) are catalyzing the interconversion of α- and β-anomers of hemiacetals of aldose sugars such as D-glucose and D-galactose, and are presumed to play an auxiliary role in carbohydrate metabolism as mutarotation occurs spontaneously in watery solutions. The first step in the Leloir pathway of D-galactose breakdown is preceded by accelerated conversion of β-D-galactopyranose into the α-anomer, the substrate of the anomer-specific D-galactose 1-kinase. Here, we identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In line with this hypothesis, LadA (AN0942), associated with the production of L-sorbose, was suggested in a recent study [74]. In our study, we predicted the same gene set involved in this oxidoreductive pathway in A. nidulans, as previously reported [79,80,82]. Although the oxidoreductive pathway for D-galactose catabolism was well established in Aspergillus species and T. reesei, knowledge of the oxidoreductive pathway in Penicillium and Basidiomycota species is scarce.…”
supporting
confidence: 85%
“…In line with this hypothesis, LadA (AN0942), associated with the production of L-sorbose, was suggested in a recent study [74]. In our study, we predicted the same gene set involved in this oxidoreductive pathway in A. nidulans, as previously reported [79,80,82]. Although the oxidoreductive pathway for D-galactose catabolism was well established in Aspergillus species and T. reesei, knowledge of the oxidoreductive pathway in Penicillium and Basidiomycota species is scarce.…”
supporting
confidence: 85%
“…Recently, we have shown that an intracellular galactose-1-epimerase (GalmB: Locus AN3432; EC 5.1.3.3), which interconverts the αand β-anomers of D-galactose in solution, contributes to the flux through the Leloir pathway (Kulcsár et al, 2017). The last three enzymes of the Leloir pathway have important anabolic functions in the production of cell wall precursors UDP-glucose and UDP-galactose (El-Ganiny et al, 2010).…”
Section: Selection Of Diagnostic Genes Of D-galactose-and L-arabinose Catabolismmentioning
confidence: 99%
“…Galactose, though a non-preferred carbon source, is usually converted to bioavailable molecules including glucose and fructose derivatives ( Kulcsár et al, 2017 ). UDP-glucose is catalyzed into UDP-galactose and galactose-1-phosphate in the presence of GALT, then the UDP-galactose would be converted into UDP-glucose under the catalysis of GALE ( Schuler et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%